2010
DOI: 10.1038/hr.2010.64
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive effects of Ocimum basilicum L. (OBL) on blood pressure in renovascular hypertensive rats

Abstract: Ocimum basilicum L. (OBL), sweet basil, is a medicinal herb used in traditional Chinese medicine to treat cardiovascular diseases including hypertension. The objective of the study was to investigate the possible antihypertensive effects of OBL extract in renovascular hypertensive rats. The two-kidney one-clip (2K1C) Goldblatt model of renovascular hypertension was used in Wistar rats. Rats were randomized into sham, untreated 2K1C, captopril-(30 mg kg À1 per day orally) and OBL-(100, 200, 400 mg kg À1 per day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 16 publications
0
24
0
3
Order By: Relevance
“…In addition to being used as food flavorings, these plants are also used as folk medicines to alleviate diseases, including hypertension 1-4 . However, mechanisms by which these plants and, in particular, eugenol are clinically beneficial are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being used as food flavorings, these plants are also used as folk medicines to alleviate diseases, including hypertension 1-4 . However, mechanisms by which these plants and, in particular, eugenol are clinically beneficial are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These plants possess antihypertensive properties, although the chemicals mediating this effect have not been elucidated (Grover et al, 2002;Umar et al, 2010;Ranasinghe et al, 2013). Eugenol and capsaicin share a vanillyl group as an important structural motif for bioactivity.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the hypotensive action of Capparis cartilaginea has been suggested to be mediated through direct relaxant action on myocardium and blood vessels (Gilani and Aftab, 1994). A similar mechanism has been suggested for the hypotensive effect of Ocimum basilicum (Aftab, 2006) along with involvement of Endothelin converting enzymes (ECEs) (Umar et al , 2010). Eugenol from the plant was isolated and was shown to be responsible for observed effects.…”
Section: Traditional Medicinal Plants With Reported Mode Of Action Wmentioning
confidence: 95%